2018
DOI: 10.1016/j.nonrwa.2017.10.008
|View full text |Cite
|
Sign up to set email alerts
|

On a Navier–Stokes–Fourier-like system capturing transitions between viscous and inviscid fluid regimes and between no-slip and perfect-slip boundary conditions

Abstract: We study a generalization of the Navier-Stokes-Fourier system for an incompressible fluid where the deviatoric part of the Cauchy stress tensor is related to the symmetric part of the velocity gradient via a maximal monotone 2-graph that is continuously parametrized by the temperature. As such, the considered fluid may go through transitions between three of the following regimes: it can flow as a Bingham fluid for a specific value of the temperature, while it can behave as the Navier-Stokes fluid for another … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…The numerical solution of the corresponding governing equations is investigated in Janečka et al [29], while a rigorous numerical analysis for various models that fall into this class is discussed in Diening et al [30], Stebel [31], Hirn et al [32], Süli and Tscherpel [33], Farrell et al [34], Farrell and Gazca-Orozco [35]. A rigorous mathematical theory for some of the aforementioned models is developed in Bulíček et al [21,36] and Maringová and Žabenský [37]; see also Blechta et al [38] for a recent review.…”
Section: Fluidsmentioning
confidence: 99%
“…The numerical solution of the corresponding governing equations is investigated in Janečka et al [29], while a rigorous numerical analysis for various models that fall into this class is discussed in Diening et al [30], Stebel [31], Hirn et al [32], Süli and Tscherpel [33], Farrell et al [34], Farrell and Gazca-Orozco [35]. A rigorous mathematical theory for some of the aforementioned models is developed in Bulíček et al [21,36] and Maringová and Žabenský [37]; see also Blechta et al [38] for a recent review.…”
Section: Fluidsmentioning
confidence: 99%
“…It was well documented that in certain situations the Navier slip boundary conditions are more appropriate than no slip boundary conditions, we refer e.g. to [12,20,23,25] or [36] and references therein. In addition, it was shown that the Navier slip boundary condition can be understood as an asymptotic limit of no slip boundary conditions in case we consider rough and highly oscillating boundary, see e.g.…”
Section: First Of All Letmentioning
confidence: 99%
“…Nevertheless, since we shall always deal with formulation without the pressure (see the De nition), we can also treat the Dirichlet boundary condition, as well as very general implicitly speci ed boundary conditions see e.g. [12,13,36] or [8]. The Neumann boundary condition for B is considered here only for simplicity and without any speci c physical meaning.…”
Section: First Of All Letmentioning
confidence: 99%
“…As to the question of existence of solutions, for any time interval and any reasonable set of data, a satisfactory theory, within the context of weak solutions, has been established during the last fifty years for a general class of fluids given by (2.2) with a continuous monotone function G (see [30,8,25,27,28,31,4,2,34,35,19,7,43,13,3,5,6,40]).…”
Section: Incompressible Non-newtonian Fluids: a Brief Overviewmentioning
confidence: 99%